Smart devices to measure and monitor QT intervals - Hoek, Leendert J.; Brouwer, Jan Leendert P.; Voors, Adriaan A.; Maass, Alexander H. (Frontiers in Cardiovascular Medicine, 2023)
Careful monitoring of the QT interval is important to monitor patients with long QT syndrome and during treatment with potentially QT-prolonging medication. It is also crucial in the development of novel drugs, in particular in case of a potential side effect of QT-prolongation and in patients with increased risk of QT-prolongation. The 12-lead electrocardiogram (ECG) is the gold standard to evaluate cardiac conduction and repolarization times. Smart watches and smart devices offer possibilities for ambulatory ECG recording, and therefore measurement and monitoring of the QT interval.We performed a systematic review of studies about smart watches and smart devices for QTc analysis.We reviewed PubMed for smart watches and smart devices that can be used to measure and monitor the QT interval. A total of 31 studies were included. The most frequent devices were 1) the KardiaMobile 6L, a FDA approved device for QTc analyses that provides a 6 lead ECG; 2) the Apple watch, a smart watch with an integrated ECG tool which allows recording of a single-lead ECG and 3) the Withings move ECG scanwatch, an analog watch with an built-in single lead ECG. The Kardia 6L and the Apple watch provide accurate measurements of the QT interval , although the Apple Watch is studied in standard and non-standard positions, and accuracy of QT measurements increased when the smartwatch was moved to alternative positions. Most studies were performed in patients and limited results are available from healthy volunteers.